A Fresh Start or a False Dawn? Assessing the Crime-Preventive Effect of Debt Settlements for People With a History of Conviction - Gålnander, Robin (The British journal of criminology, 2025)
People with convictions often face financial challenges, which hinder desistance from crime as they have few legal opportunities to address their financial burdens. In some countries, those severely insolvent can apply for ‘debt settlement’ through Enforcement Authorities. This study explores whether such settlements are crime-preventative for people with conviction histories. Analyzing Swedish administrative data and a sample of 1,621 previously convicted applicants in 2016-17, we match and compare reconviction rates between approved and declined cases. Approved cases show much lower reconviction rates, but this effect diminishes rapidly, virtually disappearing within six months. These findings prompt a discussion of the helpfulness of debt settlements for people wanting to desist from crime. Implications for future research, policy, and practice are discussed.